Evaluation Analysis of Teacher Competency Test Results (UKG) with the CIPP Model in East Luwu Regency - Andi Taufiq Umar; Danny Ajar Baskoro; Rossy Pratiwy Sihombing (PT FORMOSA CENDEKIA GLOBAL, 2022)
The teaching profession as the spearhead of a country's education continues to receive attention, especially efforts to increase self-development and professionalism. Teacher Competency Test (UKG) is a program developed in order to map teacher abilities, both pedagogic abilities and professionalism. This research was conducted with the aim of evaluating the implementation of the UKG program in East Luwu Regency, which included the implementation process, the obstacles experienced and their causes, and the results obtained. Thus, this research is expected to provide information that can be used as an alternative in planning and implementing UKG in the future. This study uses the CIPP evaluation model, which includes Context, Input, Process, Product. The results showed that the percentage of teachers who met the graduation standard was 33.98% and 66.02% did not fulfill it with a score below 55.